Protein quality assessment with a loss function designed for high-quality decoys - Roy, Soumyadip; Ben-Hur, Asa (Frontiers in Bioinformatics, 2023)
The prediction of protein 3D structure is essential for understanding protein function, drug discovery, and disease mechanisms; with the advent of methods like AlphaFold that are capable of producing very high quality decoys, ensuring the quality of those decoys can provide further confidence in the accuracy of their predictions.In this work we describe Q ϵ , a graph convolutional network that utilizes a minimal set of atom and residue features as input to predict the global distance test total score (GDTTS) and local distance difference test score (lDDT) of a decoy. To improve the model's performance, we introduce a novel loss function based on the ϵ-insensitive loss function used for SVM-regression. This loss function is specifically designed for the characteristics of the quality assessment problem, and provides predictions with improved accuracy over standard loss functions used for this task.Despite using only a minimal set of features, it matches the performance of recent state-of-the-art methods like DeepUMQA.